Serum miR-342-3p Acts as a Biomarker for Systemic Lupus Erythematosus and Participates in the Disease Progression - You M; Zhang L; Ding J (Dove Medical Press, 2023)
Min You, Long Zhang, Junxiao Ding Department of Dermatology, Affiliated Hospital of Gansu Medical College, Pingliang, Gansu, People's Republic of ChinaCorrespondence: Junxiao Ding, Department of Dermatology, Affiliated Hospital of Gansu Medical College, No. 296, Kongtong East Road, Kongtong District, Pingliang, Gansu, 744000, People's Republic of China, Tel +86-0933-8613787, Fax +86-0933-8613787, Email junxiaodinggs@163.comPurpose: The aim of this study was to investigate the diagnostic ability and prognostic value of miR-342-3p in SLE patients by detecting the expression level of serum miR-342-3p in SLE patients.Patients and Methods: The expression level of serum miR-342-3p in all subjects was determined by qRT-PCR technology, and the correlation of miR-342-3p with SLEDAI scores was evaluated using Spearman correlation coefficient. The diagnostic value of miR-342-3p in SLE was assessed using ROC curve. The prognostic value of miR-342-3p in SLE patients was analyzed by Kaplan-Meier survival curve and multivariate COX regression.Results: The qRT-PCR results showed that the expression level of serum miR-342-3p in SLE patients was significantly lower than that in healthy controls (P < 0.001). Serum miR-342-3p expression level was negatively correlated with SLEDAI scores (r = - 0.810, P < 0.001). The ROC curve suggested that serum miR-342-3p expression level was discriminative between SLE patients and healthy controls. Survival analysis results indicated that SLE patients with low serum miR-342-3p expression had a higher probability of poor prognosis of SLE (Log rank P = 0.003).Conclusion: The expression level of serum miR-342-3p was valuable in the diagnosis of SLE. Meanwhile, the low expression level of serum miR-342-3p was associated with the poor prognosis of SLE.Keywords: miR-342-3p, systemic lupus erythematosus, diagnosis, prognosis